2016
DOI: 10.1007/s10584-016-1810-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping adaptive capacity and smallholder agriculture: applying expert knowledge at the landscape scale

Abstract: The impacts of climate change exacerbate the myriad challenges faced by smallholder farmers in the Tropics. In many of these same regions, there is a lack of current, consistent, and spatially-explicit data, which severely limits the ability to locate smallholder communities, map their adaptive capacity, and target adaptation measures to these communities. To explore the adaptive capacity of smallholder farmers in three data-poor countries in Central America, we leveraged expert input through in-depth mapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 25 publications
(28 reference statements)
0
34
0
7
Order By: Relevance
“…Our parallel field survey of farm practices used by these smallholder farmers [53] found that smallholder farmers with insecure land tenure were less likely to have implemented adaptation strategies than those farmers who owned their land, because they were unwilling to make long-term investments in practices that yield longterm benefits. Insecure land tenure, limited capital, low education, and lack of access to financial and technical support have also been identified as key constraints to adaptation elsewhere [e.g., 6,16,54,55]. The fact that farmers identified the need for government support in providing agricultural inputs, technical support, training, and access to finance further corroborates that these factors serve as constraints to farmer adaptation.…”
Section: (244)mentioning
confidence: 90%
See 2 more Smart Citations
“…Our parallel field survey of farm practices used by these smallholder farmers [53] found that smallholder farmers with insecure land tenure were less likely to have implemented adaptation strategies than those farmers who owned their land, because they were unwilling to make long-term investments in practices that yield longterm benefits. Insecure land tenure, limited capital, low education, and lack of access to financial and technical support have also been identified as key constraints to adaptation elsewhere [e.g., 6,16,54,55]. The fact that farmers identified the need for government support in providing agricultural inputs, technical support, training, and access to finance further corroborates that these factors serve as constraints to farmer adaptation.…”
Section: (244)mentioning
confidence: 90%
“…We focused our study on coffee and basic grains as these the two most common types of smallholder systems in the region [39]. We characterized landscapes as having low adaptive capacity using expert mapping interviews, validation workshops, and expert online surveys, in which experts from the region characterized landscapes based on 20 variables (representing natural, human, social, physical, and financial capital) that contributed to farmer adaptive capacity (see [6] for details). The Turrialba and Los Santos landscapes are dominated by smallholder coffee production, Choluteca is dominated by basic grain production, while the remaining landscapes (Yoro, Chiquimula, and Acatenango) include a mix of coffee and basic grain production.…”
Section: Study Landscapesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouroncle et al (2016) address the adaptive capacity and vulnerability of smallholder agricultural livelihoods in four countries in the region at the municipality level. Holland et al (2016) present an innovative methodology, applicable in data-poor environments, for mapping the adaptive capacity of smallholder farmers to climate change at the landscape level, using expert knowledge.…”
Section: Organizations Supporting Climate Change Adaptation In the Rementioning
confidence: 99%
“…Research on GEC has rarely included local perspectives; to be precise, human experience has been excluded, and studies have focused on the use of quantitative indices that give an indirect measure of vulnerability (ArceNazario 2007), or of societies' capacity to adjust (Holland et al 2016). This would seem paradoxical, given that we humans are the central players in GEC, both as perpetrators and victims.…”
Section: Ethnobiology Is Inclusivementioning
confidence: 99%